Effects of prenatal small-quantity lipid-based nutrient supplements on pregnancy, birth and infant outcomes: A systematic review and meta-analysis of individual participant data from randomized controlled trials in low- and middle-income countries - Dewey, Kathryn G.; Wessells, K. Ryan; Arnold, Charles D.; Adu-Afarwuah, Seth; Arnold, Benjamin F.; Ashorn, Per; Ashorn, Ulla; Garcés, Ana; Huybregts, Lieven; Krebs, Nancy F.; Lartey, Anna; Leroy, Jef L.; et al. (Elsevier, 2024)
Background Undernutrition during pregnancy increases the risk of giving birth to a small vulnerable newborn. Small-quantity lipid-based nutrient supplements (SQ-LNS) contain both macro- and micronutrients and can help prevent multiple nutritional deficiencies.